Analisis Perbedaan Perilaku Konsumen Dalam Perspektif Konvensional dan Islam - yulpida Sari Lubis; M. Irwan Padli Nasution (Economic Reviews Journal, 2023)
This study was conducted to find out about the differences and ways of consumption behavior in an Islamic perspective and in a conventional perspective as well. In this case consumer behavior is a feature related to buying and using products for their needs. And this consumer behavior arises because of several basic principles. to meet needs and also satisfaction for individuals or groups of problems in this research how a consumer from a conventional and Islamic economic perspective. In Islam itself this consumer behavior is a job that satisfies needs that highlight a will with the principles of Islamic law. Islam also consumption activities are very obligatory to have like maslahah either for our personality or for other people. This maslahah is to fulfill human needs and according to sharia law and unite the good and the harmless and must balance the world and hereafter. Keywords: consumer behavior, Islamic economics, conventional economics